Assessing the sensitivity of physiographical parameters in modeling hydrological ecosystem services that support food security: The case of Vietnamese Mekong Delta - Sreejita Banerjee; Ho Hu Loc; Indrajit Pal; Anirban Mukhopadhyay; Thanh Van Pham Huynh; Duy Tien Pham; Hong Cam Nguyen Thi (Modeling Earth Systems and Environment, 2025)
Vietnamese Mekong Delta (VMD) experiences high soil loss and nutrient export, which in turn impacts food security and livelihood. These parameters play an important role in hydrological ecosystem services. Using the InVEST modeling software, we quantify and map sediment and nutrient regulation, as well as seasonal water yield, across the VMD. We propose an innovative approach for model validation, tailored to regions with limited data availability, that utilizes observed data to enhance the accuracy and reliability of the model. The results of this study indicate that approximately 65% of the total watershed is prone to high nutrient export, and 33% of the area is prone to soil erosion. Sensitivity analysis for the model parameters reveals that variations in k (nutrient delivery ratio, sediment delivery ratio) and β (seasonal water yield) have the most significant effects on sediment export and baseflow, respectively. This study focuses on regulating ecosystem services in agricultural regions that contribute to Vietnam’s food production. This study presents a series of implications and findings that contribute to the overall understanding of how hydrological ecosystem services can support food security in data-scarce regions, as well as offer recommendations to policymakers on the application of nature-based solutions and the sustainable management of water resources.